Evaluation of the clinical features of children diagnosed with IgE-mediated food allergy - Kilic, Mehmet; Taskin, Erdal (Bilimsel Tip Yayinevi, 2015)
Objective: The prevalence of food allergies differs among countries. In addition, data on allergic diseases that accompany food allergies are limited. We aimed to evaluate demographic, clinic, and phenotypic features in children diagnosed with IgE-mediated food allergies. Materials and Methods: The charts for 186 children diagnosed with IgE-mediated food allergies at the allergy clinic between February 2008 and July 2013 were retrospectively reviewed. Results: The most common food allergies in the children were egg whites (49.2%), cow's milk (42.3%), egg yolks (7.7%), peanuts (5.4%), soy (3.8%), hazelnuts (3.8%), sesame (3.8%), lentils (3.1%), and fish (3.1%). Isolated egg allergies were more common than isolated milk allergies in patients with asthma (p<0.0001). Total IgE levels, peripheral eosinophil count, and history of gastrointestinal symptoms were higher in patients with multiple food allergies than in patients with mono-food allergies (p<0.01, p=0.015, p<0.001, respectively). We found that the risk of developing asthma was 2.8-fold higher in patients diagnosed with food allergies and rhinitis (OR: 2.80, 95%; CI: 1.90-6.20; p=0.01). Conclusion: Th is study showed that the type, incidence, and clinical symptoms of IgE-mediated food allergies were heterogeneous.
Keywords: Food allergy; child; IgE-mediated hypersensitivity; egg; milk; peanut